Analisis Perbandingan PDB, Konsumsi, Investasi, dan Ekspor Neto di Indonesia Pada Era Presiden Susilo Bambang Yudhoyono dan Era Presiden Joko Widodo - Jodi Rizki Kusuma (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2020)
This research want to test economic condition betwen two president, Susilo Bambang Yudhoyono and Joko Widodo, on their fisrt period. GDP, comsumption, investation, and net export is become a variable in this economic calculations. Sample was taken from the first period of each periode president. With period of time 2005-2009, and 2015-2019. Time series data analysis using data from third parties, and test using independent sample t-test. The result of research found that the GDP, consumption, investation, and net export have a significant diference of each variable. Result of research an explanation that government work programs that focus on economic equity show an increase in GDP, consumption & investment. Meanwhile, the government work program that focuses on domestic stabilization shows that net exports have increased.